Dataset of the paper "Numerical modelling-based damage diagnostics in cultural heritage structures" - D'Altri, Antonio Maria; de Miranda, Stefano; Castellazzi, Giovanni; Glisic, Branko (University of Bologna, 2023)
This dataset, developed as part of the Horizon 2020 HOLAHERIS project, contains data, models and results related to a numerical modelling-based damage diagnostics methodology for cultural heritage structures. A 3D documentation data integration is developed to swiftly generate numerical models of heritage structures using point clouds and virtual tours. This approach enables the utilization of incomplete point cloud data, such as those limited to outer surfaces, for generating solid finite element models. Any missing information is supplemented using interactive and immersive frameworks off-site. Subsequently, various nonlinear static and dynamic analyses are conducted on the solid model to assess different load scenarios (e.g., earthquakes, soil settlements) employing a nonlinear continuum constitutive law. Additionally, a crack pattern matching indicator is introduced to quantitatively identify the probable load scenario responsible for the observed damage pattern in the heritage structure by comparing numerical and actual crack patterns. This methodology facilitates the rapid generation and extraction of numerical models reflecting the current damaged state of the structure and identifies vulnerable areas susceptible to further damage. Models and structural analysis results (pushover curves) related to a meaningful benchmark, i.e., Morris Island lighthouse in South Carolina (USA), are also collected herein.